2019
DOI: 10.7554/elife.47490
|View full text |Cite
|
Sign up to set email alerts
|

Hemimetabolous insects elucidate the origin of sexual development via alternative splicing

Abstract: Insects are the only known animals in which sexual differentiation is controlled by sex-specific splicing. The doublesex transcription factor produces distinct male and female isoforms, which are both essential for sex-specific development. dsx splicing depends on transformer, which is also alternatively spliced such that functional Tra is only present in females. This pathway has evolved from an ancestral mechanism where dsx was independent of tra and expressed and required only in males. To reconstruct this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(141 citation statements)
references
References 127 publications
(195 reference statements)
9
131
1
Order By: Relevance
“…Our analysis of RNA-seq data suggests that the cockroach X chromosome may be dosage compensated in males-we find no evidence for reduced expression of element F homologs in male cockroaches, regardless of whether the genes appear to be haploid in males (Figure 4). Previous work found evidence that the cockroach tra homolog may regulate dosage compensation because knockdown of tra in cockroach females results in female-specific lethality of their progeny [68]. Here, we found that homologs of genes involved in regulating expression of element F genes in flies are present in the cockroach genome, with their functional domains conserved ( Figure 5).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our analysis of RNA-seq data suggests that the cockroach X chromosome may be dosage compensated in males-we find no evidence for reduced expression of element F homologs in male cockroaches, regardless of whether the genes appear to be haploid in males (Figure 4). Previous work found evidence that the cockroach tra homolog may regulate dosage compensation because knockdown of tra in cockroach females results in female-specific lethality of their progeny [68]. Here, we found that homologs of genes involved in regulating expression of element F genes in flies are present in the cockroach genome, with their functional domains conserved ( Figure 5).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, the master regulators of Drosophila sex determination almost certainly differ from the sex determiners in the MRCA of brachyceran flies, which likely used a Y-linked male-determiner ( Figure 1). Moreover, the sexually dimorphic splicing of the sex determination pathway gene tra differs between German cockroach and flies [68]. Therefore, we hypothesize that B. germanica has a homologous X chromosome with the MRCA of brachyceran flies, but the sex determination system is not conserved between cockroaches and flies.…”
Section: Sex In B Germanica Is Likely Determined By X Chromosome Dosmentioning
confidence: 90%
“…Sexual differentiation occurs following subsequent signals that further directs the primary sex-determining signal to the development of specific traits that are sexually dimorphic [104][105][106]. These signals can either be environmental or genetic [107][108][109][110]. The evolution and conservation of these signals are currently being resolved through comparative genomics and experimentally by using developmental genetics.…”
Section: Intersexual Variation Of the Venom Systemmentioning
confidence: 99%
“…dsx is involved in male-type color pattern formation, but not in female-specific gynomorphic coloration in I. senegalensis . The male dsx isoform is essential for male differentiation in most insects, while the female dsx isoform is involved in female differentiation only in holometabolous insects (Wexler et al, 2019; Zhou, Whitworth, Pozmanter, Neville, & Doren, 2018). Our results are consistent with previous work on male differentiation.…”
Section: Discussionmentioning
confidence: 99%